Comparison of outbreak and nonoutbreak Acinetobacter baumannii strains by genotypic and phenotypic methods. - Dijkshoorn, L (1996)
Thirty-one Acinetobacter baumannii strains, comprising 14 strains from 14 outbreaks in different northwestern European cities and 17 sporadic strains, were compared by investigating various properties of the strains including biotype, antibiogram, cell envelope protein electrophoretic profile, ribotype pattern, and the band pattern generated by a novel genomic fingerprinting method, named AFLP, which is based on the selective amplification of restriction fragments. Results showed that 12 strains from unrelated outbreaks were linked together in two clusters according to their similarities by these typing methods, whereas sporadic strains were more heterogeneous. Outbreak strains appeared to be markedly more resistant to antibiotics than nonoutbreak strains. The uniformity of typing characters in two sets of outbreak strains suggests that strains in each cluster have a common clonal origin.